ANALYSIS OF APPLICATION ARTICLE 88 REGULATION OF THE MINISTER OF HOME AFFAIRS NUMBER 120 OF 2018 CONCERNING AMENDMENT TO REGULATION OF THE MINISTER OF HOME AFFAIRS NUMBER 80 OF 2015 CONCERNING THE ESTABLISHMENT OF REGIONAL LEGAL PRODUCTS - Linjte Marpaung; Herlina Ningrum; Erman Syarif (PRANATA HUKUM, 2021)
Enforcement of the concept of law facilitation of its implementation has not gone well, especially the implementation of the order Article 88 Regulation of the Minister of Home Affairs No. 80 of 2015 on the Establishment of Regional Law Products in conjunction with Minister of Home Affairs Regulation Number 120 Year 2018. The problem of how the legal consequences and obstacles in the application of Article 88 Minister of Home Affairs Regulation No. 120 of 2018 concerning Amendment to Regulation of the Minister of Home Affairs Number 80 Year 2015 concerning the Establishment of Regional Law Products against the preparation of regional legal products in Lampung Province. Research methods use normative and empirical juridical approaches. Norms must be stated in Article 88 paragraph (2) Regulation of the Minister of Home Affairs No. 120 of 2018 states that facilitation of draft local regulations and draft regulations of regional heads and / or draft regulations of the DPRD has the consequence that facilitation must be implemented, if there is no law on the draft regional regulations and draft regulations of regional heads and / or draft regulations of the DPRD flawed procedures both material (substantial) and formal (procedural) and can not be determined and delay in facilitation resulting in all the implementation process of the draft regional regulations and the draft regulation of regional heads and / or draft regulations of the DPRD. Advice to the Directorate General of Regional Law Products Otda of the Ministry of Home Affairs to prepare sop evaluation, facilitation of regional legal products, simplification of procedures.